A Systematic Literature Review on the Influence of Geology and Geotechnical Parameters in Blast Design Optimization - Aprilliana; Y. Maulana (Mataram University, 2026)
Blasting is a critical operation in mining and civil engineering projects, and its effectiveness is strongly influenced by both blasting parameters and the geological characteristics of the rock mass. However, conventional blast design approaches often rely mainly on empirical guidelines and explosive parameters, while the variability of geological and geotechnical conditions is frequently underrepresented in the design process. Therefore, this study aims to systematically review and synthesize existing scientific literature on the influence of geological and geotechnical parameters in blast design optimization in order to identify key controlling factors, research trends, and technological developments that support more efficient and environmentally responsible blasting practices. This research adopts a systematic literature review approach based on established review procedures. Relevant scientific publications were collected from major academic databases, particularly Scopus indexed journals, using structured search strings applied to article titles, abstracts, and keywords. The selected studies were screened and analyzed, and the findings were synthesized into several thematic categories related to geological conditions, rock mass properties, blasting performance, environmental impacts, and emerging technologies in blast design optimization. The results show that geological and geotechnical parameters such as rock strength, discontinuity characteristics, structural geology, and rock mass classification significantly influence blasting outcomes, including rock fragmentation, explosive energy distribution, ground vibration, and flyrock generation. The findings also highlight the importance of the interaction between blast design parameters and geological variability in determining blasting efficiency. In addition, recent technological developments, including Measurement While Drilling systems, numerical modeling techniques, and machine learning based predictive models, have improved the integration of geological information into blast design optimization. The novelty of this study lies in its comprehensive synthesis of interdisciplinary research that integrates geological characterization, geotechnical analysis, and blasting engineering within a unified conceptual framework. This study contributes to the advancement of blasting research by providing an integrated understanding of the role of geological and geotechnical parameters in blast design optimization and by highlighting the transition toward data driven and geology informed blasting strategies in modern mining operations.